Recovery of coffee seedlings (Coffeea arabica L.) in tubets through pruning - Carvalho, Alex Mendonça de; Guimarães, Rubens José; Moura, Cesar Augusto de; Mendes, Antonio Nazareno Guimarães; Carvalho, Gladyston Rodrigues de (Coffee Science - ISSN 1984-3909, 2007)
Coffee seedlings are frequently lost when left in the nursery after the ideal planting time, although research has shown that they may be recovered when grown in polyethylene bags. The objective of this work was to compare polyethylene bags and tubets as recipients for the recovery of coffee seedlings kept in a nursery for late planting through pruning. The experiment was carried out at the Coffee Sector of UFLA (Lavras Federal University) from August 2003 to December 2004. Coffee (Coffea arabica L.) Rubi cultivar seedlings at the 7 to 9 leaves stage, characterizing old seedlings, were used. The experimental design was a randomized experimental block design in a factorial scheme of 2x3+1, with two seedling diameters (below and above 4mm), three pruning times (April, July, and September) and two additional treatments: new seedlings in April and July. Each plot was constituted by 13 seedlings and the five central ones were used for evaluations. Sprout number, size and diameter; nod number, leaf area, and above ground and root dry weights were evaluated during the course of the experiment. It was concluded that the old seedlings that remained in nurseries, when grown in tubets, may be used for late planting when pruned accordingly and show better development than traditional half-year seedlings. The seedlings with small diameters pruned in April presented the best development.